Leaf water potential and growth of Eucalyptus globulus planted with different density - Donoso, S.; Ruiz, F. (Bosque (Valdivia), 2001)
In a trial established in 1996, representing five different Eucalyptus globulus spacings (4.0 m x 1.5 m, 4,0 m x 2,25 m, 4,0 m x 3,0 m, 4,0 m x 4,0 m and 4,0 m x 5,0 m), the DBH and height of the trees was evaluated monthly during the third year of growth. At the same time, pre-dawn leaf water potential and the amount of available soil water was measured. The growth in height, diameter and basal area in the smaller spacing at the beginning of May was low in relation to the other treatments, decreasing until stopping at the end of summer, then restarting with the first rains. In all treatments a marked summer stress was observed and, in the smaller spacing, trees generally died at the end of summer. The pre-dawn water potential presented a better relation with the available water at the 20-40 cm layer than with the 0-20 cm layer.